Impact of Disaster Events on The Development of Tourism in Jammu and Kashmir Since1990 - Parveen, Shazia; Kh. Moirangleima; Wagay, Rouf Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
The tourism sector has played a crucial role in connecting J&K with the global community, providing new opportunities for investment and revenue generation. This has not only led to the creation of jobs and socio-economic development for the local population but has also contributed significantly to poverty reduction and sustainable growth. Tourism is a key component of the economy, making a substantial contribution to the State GDP as a multibillion-dollar industry. Additionally, it serves as a major source of employment, directly and indirectly employing around 60% of the population in the absence of a strong industrial sector. The Jammu region, known for its temples, attracts a large number of pilgrims year-round. However, the tourism sector is influenced by a variety of factors, both internal and external, that impact the industry. Natural disasters and unforeseen events are prime examples of such factors, as they can have profound effects on individuals, society, and tourist flows. These disasters can strain government resources and social stability, significantly affecting the state's tourism industry, which is crucial for the overall economy. This study aims to explore the impact of natural and man-made disasters on tourism in Jammu and Kashmir, as well as strategies to mitigate their adverse effects.